Pengaruh Celebrity Endorser terhadap Brand Image Produk Kartu Seluler Prabayar As Telkomsel Di Kota Pontianak - B11108055, Rita Hilariya (Jurnal Manajemen Update, 2012)
This study aimed to determine the influence celebrity endorser for the brand image of the product As telkomsel prepaid mobile cards in Pontianak.The research population is all the people who live in the city of Pontianak and samples taken for this study as many as 100 people. The research method used is descriptive and quantitative research using questionnaires as data collection techniques. The variables in this study include three independent variables (X), namely Credibility (X1), attractiveness (X2), Power (X3) and the dependent variable (Y) is the Brand Image (Y).The results of this study, it can be concluded that simultaneous independent variable (X) is Credibility (X1), Attractiveness (X2), Power (X3) have a significant effect on brand image (Y). Then it can be concluded that the partially independent variable (X) is Credibility (X1) and Power (X3) have an influence on brand image (Y) while the attractiveness (X2) had no significant effect on brand image (Y). Keywords : Celebrity Endorser, Brand Image